2022
DOI: 10.3390/nu14214682
|View full text |Cite
|
Sign up to set email alerts
|

Iron: Not Just a Passive Bystander in AITD

Abstract: Autoimmune thyroid disease (AITD) is the most prevalent autoimmune disease all over the world and the most frequent cause of hypothyroidism in areas of iodine sufficiency. The pathogenesis of AITD is multifactorial and depends on complex interactions between genetic and environmental factors, with epigenetics being the crucial link. Iron deficiency (ID) can reduce the activities of thyroid peroxidase and 5′-deiodinase, inhibit binding of triiodothyronine to its nuclear receptor, and cause slower utilization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 148 publications
0
3
0
Order By: Relevance
“…Currently, our knowledge about thyroidal uptake, utilization and potential storage mechanisms for Se und Fe, and the interaction of such mechanisms with the thyroid utilization and homeostasis of the iodine system is lacking and thus purposeful basic and clinical research on these relevant interactions is urgently needed. Only limited experimental and clinical evidence for the need of a balanced supply of I and Fe on the one hand [ 12 , 52 , 113 , 114 , 117 ], and of I and Se on the other hand [ 43 , 113 , 118 , 119 ], has been reported. Thus, inadequate Fe status impairs the utilization of I, even if this element is sufficiently available.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, our knowledge about thyroidal uptake, utilization and potential storage mechanisms for Se und Fe, and the interaction of such mechanisms with the thyroid utilization and homeostasis of the iodine system is lacking and thus purposeful basic and clinical research on these relevant interactions is urgently needed. Only limited experimental and clinical evidence for the need of a balanced supply of I and Fe on the one hand [ 12 , 52 , 113 , 114 , 117 ], and of I and Se on the other hand [ 43 , 113 , 118 , 119 ], has been reported. Thus, inadequate Fe status impairs the utilization of I, even if this element is sufficiently available.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the decreased expression of histone deacetylase HDAC2 in eye tissue of patients with thyroid eye disease leads to the increased proliferation of T cells and worsening of inflammation 19 . Another research study has indicated that miR-133a, through the RhoA/ROCK signaling pathway, can influence cell contraction and proliferation, thereby affecting the occurrence and development of thyroid eye disease 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Hashimoto’s thyroiditis (HT), also known as chronic lymphocytic thyroiditis and Hashimoto’s disease, is an autoimmune thyroid disease (AITD) with a complex etiopathology, which includes genetic (e.g., major histocompatibility complex (MHC) genes) and environmental factors, such as past infections, medications, and smoking, and the level of microelements, such as iodine, iron, and selenium [ 1 , 2 ]. With an incidence of 0.3–1.5 cases per 1000 people, HT is the most common cause of hypothyroidism in iodine-replete areas [ 3 ].…”
Section: Introductionmentioning
confidence: 99%